Microbiome–environment interactions in antimony-contaminated rice paddies and the correlation of core microbiome with arsenic and antimony contamination. (January 2021) - Li, Baoqin; Xu, Rui; Sun, Xiaoxu; Han, Feng; Xiao, Enzong; Chen, Lei; Qiu, Lang; Sun, Weimin
Abstract: Mining activities of antimony (Sb) and arsenic (As) typically result in severe environmental contamination. These contaminants accumulate in rice and thus threaten the health of local residents, who consume Sb- and As-enriched rice grains. Microorganisms play a critical role in the transformation and transportation of Sb and As in paddy soil. Thus, an understanding of the microbiology of contaminated sites would promote the production of safe agricultural products. In this study, six Sb- and As-contaminated rice fields near an active Sb-mining area were investigated. The Sb and As concentrations of all samples were elevated compared to the background level in China. Nitrate, total As, total Sb, and Fe(III) were the major determinants of the microbial community structure. Seven bacterial taxa (i.e. Bradyrhizobium, Bryobacter, Candidatus Solibacter, Geobacter, Gemmatimonas, Halingium, and Sphingomonas ) were identified as the core microbiome. These taxa were strongly correlated with the As and Sb contaminant fractions and likely to metabolize As and Sb. Results imply that many soil microbes can survival in the Sb/As contaminated sites. Highlights: Rice paddy was collected from various field in Sb contaminated site. Microbial communities were characterized using amplicon sequencing. Core microbiome of the paddy was obtained. Environment-microbe interaction were investigated.